2005
DOI: 10.1177/0272989x05276857
|View full text |Cite
|
Sign up to set email alerts
|

Mammographers’ Perception of Women’s Breast Cancer Risk

Abstract: Objective-To understand mammographers' perception of individual women's breast cancer risk.Materials and Methods-Radiologists interpreting screening mammography examinations completed a mailed survey consisting of questions pertaining to demographic and clinical practice characteristics, as well as 2 vignettes describing different risk profiles of women. Respondents were asked to estimate the probability of a breast cancer diagnosis in the next 5 years for each vignette. Vignette responses were plotted against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Indeed, in one study of these same radiologists, 96% overestimated an individual woman's 5- year risk of a diagnosis of breast cancer, particularly those with risk factors such as family history of breast cancer and prior biopsy (15). This suggests that radiologists may be over influenced by some risk factors when they are deciding whether or not to recall women for additional work up or are considering whether or not to biopsy a possible abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in one study of these same radiologists, 96% overestimated an individual woman's 5- year risk of a diagnosis of breast cancer, particularly those with risk factors such as family history of breast cancer and prior biopsy (15). This suggests that radiologists may be over influenced by some risk factors when they are deciding whether or not to recall women for additional work up or are considering whether or not to biopsy a possible abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…While observational studies have shown that mammography performed on women currently using postmenopausal hormone therapy (HT) have higher false positive rates (8, 15-18) and lower sensitivity (8, 18) it is not clear if this is completely caused by HT's effect on breast density or if radiologists are being influenced by the knowledge of HT use, or both. In our study, we adjusted our analyses for radiologists' interpretation of breast density.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that few of the 15,515 probably benign assessments were given to women with extremely dense breasts ( n = 1,005) or with symptoms ( n = 266 with a breast lump and n = 893 with other symptoms). Radiologists may have recommended these women for immediate follow-up because they doubted the accuracy of mammography in women with dense breasts [19, 20] or because they considered symptomatic women to be at greater than average breast cancer risk [21]. The majority of mammography malpractice suits citing delays in cancer diagnoses are initiated by women with symptoms, which could help explain the more aggressive recommendations for this group [22].…”
Section: Discussionmentioning
confidence: 99%
“…These data were derived from the respective mammography registries associated with the participating radiologists. Module 2 profiled breast cancer risk in each radiologist’s respective patient population, also ascertained from respective BCSC Sites, to illustrate how low breast cancer risk is in population-based settings, and Module 3 presented information on the possible impact of medical malpractice concerns on recall rates, which was shown in our previous research to influence recall rates (20, 21). …”
Section: Methodsmentioning
confidence: 99%